2008
DOI: 10.1159/000151765
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Sedation for Endoscopic Procedures in Patients 90 Years of Age and Older

Abstract: Background and Aim: There are only a few studies on propofol sedation for very elderly patients. The present study was undertaken to evaluate the safety of propofol sedation in patients 90 years of age and older undergoing endoscopic procedures. Methods: We prospectively assessed endoscopic procedures for patients 90 years of age and older using propofol sedation. Endoscopic procedures, dosage used, respiratory depression, complications and 30-day mortality were evaluated. In a subset of the enrolled patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
1
40
2
2
Order By: Relevance
“…Age and severe complications were not related when the patient underwent gastroscopy + colonoscopy despite the doses of propofol It could be argued that complication rate in patients ≥ 80 years is not higher than in younger patients because the dose of propofol was significantly lower in those patients. This fact is shared by several studies comparing elderly and young people (7,20,27,28,35,36). This hypothesis is supported by the fact that, as we have observed, dose increase is the only risk factor to develop complications in patients ≥ 80 years.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Age and severe complications were not related when the patient underwent gastroscopy + colonoscopy despite the doses of propofol It could be argued that complication rate in patients ≥ 80 years is not higher than in younger patients because the dose of propofol was significantly lower in those patients. This fact is shared by several studies comparing elderly and young people (7,20,27,28,35,36). This hypothesis is supported by the fact that, as we have observed, dose increase is the only risk factor to develop complications in patients ≥ 80 years.…”
Section: Discussionsupporting
confidence: 80%
“…We used the required dose to achieve deep sedation (MOAA/S score of 1) and elderly patients achieved deep sedation with a lower dose. In fact, it has been proved that elderly patients require a lower dose of propofol to reach similar plasmatic levels to younger people (20,36). The absence of differences regarding the development of sedation-related complications might be explained by the fact that we selected a healthy subgroup of octogenarians.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that low-dose propofol provides stable sedation for ERCP in patients ≥ 90 years of age 14 . A previous study performed in patients aged between 23 and 94 years reported an incidence of cardiopulmonary complications following ERCP of 4.1% in those aged 80 years, compared with 7.1% in those aged ≥ 80 years 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is a good sedative agent for endoscopic procedures, in that it is superior to benzodiazepines with regard to rapidity of induction of sedation and is associated with a faster recovery [3][4][5][6] . Propofol sedation in high risk and elderly patients undergoing endoscopic procedures has been reported to be both safe and effective [7][8][9][10][11][12][13][14][15] . The aim of this study was to evaluate the effectiveness of PEG replacement using EGD and low-dose propofol sedation in the outpatient setting.…”
Section: Introductionmentioning
confidence: 99%